PRINCIPLES OF ECONOMIC LAW - Bezzubov, Dmytro; Timush, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is a comprehensive legal analysis of the basic principles of economic law. Research methods: in the course of work the basic scientific methods of the system analysis, formal logic and a method of classifications are used. The method of systematic analysis is used to determine the content of the principles of commercial law. The method of formal logic allowed to determine scientific views on the categories of principles of economic law. The method of classifications allowed to identify ways to further improve the principles of economic relations and vectors of their legal regulation. Results: the study of the principles of economic law allows to identify ways and methods to minimize the impact of negative factors and risks on the state of the economy and law in the field of management. The results of the research presented in this scientific article allow us to determine further steps in the study of principles in the modern science of commercial law. Discussion: problems of classification, content, influence of the principles of economic relations are important from the standpoint of the development of the science of economic law. The effectiveness of legal regulation depends on a number of factors, but largely on the principles of law, as they are the primary basis, the vector that indicates the direction of legal regulation and its legal purpose. The definition and proper legal consolidation of the principles of economic law are especially relevant in this context, as they are the basis, the basis, the legal basis on which economic law is built, and the effectiveness of legal regulation in this area directly affects the state economy. The value of the principles of law is that they are able to determine the content of the legal system and its structural elements, to be a means of interpreting legal norms, as well as to directly regulate legal relations, including bridging gaps in law, which is especially relevant for commercial law due to the rapid dynamics of economic relations and the constant expansion of economic spheres. The existence of well-defined principles of commercial law, taking into account the case law of the European Court of Human Rights, and enshrined in national law, can solve this problem within the field of commercial law. The principles of law affect both the process of rule-making and the process of law enforcement. However, among practicing lawyers, the principles of law are perceived only as a theoretical, even ideological component of law, which is devoid of any practical significance. This formal approach to the principles of law is due, in particular, due to inadequate attention to this topic in courses and training of specialists in the field of law, and insufficient attention to this topic by theoretical research, which, in turn, is reflected in shortcomings as rulemaking, and law enforcement. It should also be noted that there is no article in the Commercial Code of Ukraine that would contain general principles of commercial law, which should be the regulator of public relations in the field of commercial law. The principles of economic and legal regulation not only determine the vector of such regulation, but are also used to fill existing gaps in legal regulation through the application of the analogy of law. At the level of the basic branch code it is necessary to fix the principles which would define the general conceptual bases on which all regulatory legal acts regulating economic legal relations should be built, and on the basis of which both norms of the code, and other legal acts of economic law should be interpreted. Determining the sectoral principles of commercial law, it is necessary to begin with the specifics of the branch of law, which has a complex nature of relations of the subject of regulation and, accordingly, the complex nature of economic relations. The principles of commercial law should be used to combine essentially opposite in nature legal and public interests, the simultaneous existence of which is a consequence of the complex nature of the field of commercial law. It is important to correctly determine the presence of private or public interest in real legal relations and find the optimal relationship between them. The principle of optimal balance of private and public interests should be one of the principles of commercial law. Achieving the principle of optimal balance of private and public interests is possible through the application of the general principle of proportionality.